Process evaluation of the implementation of an evidence-based model of care for low back pain in Australian emergency departments - Oliveira, Crystian B. [UNESP]; Coombs, Danielle; Machado, Gustavo C.; McCaffery, Kirsten; Richards, Bethan; Pinto, Rafael Z.; O'Keeffe, Mary; Maher, Chris G.; Christofaro, Diego G.D. [UNESP] (Elsevier, 2023)
Background: The Sydney Health Partners Emergency Department (SHaPED) trial targeted ED clinicians and evaluated a multifaceted strategy to implement a new model of care. The objective of this study was to investigate attitudes and experiences of ED clinicians as well as barriers and facilitators for implementation of the model of care. Design: A qualitative study. Methods: The EDs of three urban and one rural hospital in New South Wales, Australia participated in the trial between August and November 2018. A sample of clinicians was invited to participate in qualitative interviews via telephone and face-to-face. The data collected from the interviews were coded and grouped in themes using thematic analysis methods. Results: Non-opioid pain management strategies (i.e., patient education, simple analgesics, and heat wraps) were perceived to be the most helpful strategy for reducing opioid use by ED clinicians. However, time constraints and rotation of junior medical staff were seen as the main barriers for uptake of the model of care. Fear of missing a serious pathology and the clinicians' conviction of a need to provide something for the patient were seen as barriers to reducing lumbar imaging referrals. Other barriers to guideline endorsed care included patient's expectations and characteristics (e.g., older age and symptoms severity). Conclusions: Improving knowledge of non-opioid pain management strategies was seen as a helpful strategy for reducing opioid use. However, clinicians also raised barriers related to the ED environment, clinicians’ behaviour, and cultural aspects, which should be addressed in future implementation efforts.
Keywords: Emergency department; Evaluation study; Implementation science; Low back pain